HUBUNGAN KUALITAS PELAYANAN DENGAN TINGKAT KEPUASAN MASYARAKAT DALAM PEMBUATAN KARTU KELURAGA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUMEDANG - Noviana Sofyan; Deden Haria Garmana; Irma Hermayanty (LPPM UNSAP, 2026)
This research is motivated by the quality of service at Disdukcapil Sumedang Regency has not been running as expected. This study aims to determine how good the quality of service is, how high the community satisfaction is and how strong the relationship between service quality and community satisfaction is. The method used in the preparation of this thesis is this research method using descriptive methods. This research variable uses an independent variable (service quality) and a dependent variable (community satisfaction). The population and sample in this study were people who made Family Cards totaling 60 people. The method used is literature study, field study (observation and questionnaire). Based on the research results that the quality of service is 85.55% (very good). Community satisfaction is 85.65% (very good) and the relationship between service quality and community satisfaction is at a very strong correlation level or 0.895, hypothesis testing that tcount is greater than ttable, namely 1.67065> 6.327, meaning that there is a positive and significant relationship between service quality and community satisfaction and the amount of service quality to community satisfaction in making Family Cards at the Population and Civil Registration Office of Sumedang Regency is 80.2% (very strong) and there are still 9.8% other factors not examined by the author.